Progress of autonomic disturbances in narcolepsy type 1 - Wang, Ying; Sun, Qingqing; Tang, Qi; Zhang, Yanan; Tang, Mingyang; Wang, Dong; Wang, Zan (Frontiers in Neurology, 2023)
Narcolepsy type 1 is a kind of sleep disorder characterized by a specific loss of hypocretin neurons in the lateral hypothalamus and reduced levels of hypocretin-1 in the cerebrospinal fluid. Hypocretin deficiency is associated with autonomic disorders. This article summarizes the autonomic disorders and possible mechanisms associated with narcolepsy type 1. Patients with narcolepsy type 1 often have various systemic autonomic symptoms, including non-dipping blood pressure, reduced heart rate variability, dynamic cerebral autoregulation impairment, reduced gastric motility and emptying, sleep-related erectile dysfunction, skin temperature abnormalities, and blunted pupillary light reflex. Similar findings should strengthen the recognition and intervention of these disturbances in clinical practice. In addition to hypocretin deficiency, current evidence also indicates that pharmacological therapy (including psychostimulants and anti-cataplectic drugs) and comorbidities may contribute to the alterations of autonomic system observed in narcolepsy type 1.